Concept of ecologically acceptable chromatographic methods: Case study on the separation of dronedarone hydrochloride and its degradation products - Djajić, Nevena; Krmar, Jovana; Stojanović, Jevrem; Svrkota, Bojana; Otašević, Biljana; Malenović, Andjelija; Protić, Ana (Archives of Pharmacy, 2024)
Recently, concern about the environmental impact of drug analysis methods has increased significantly. Reversed-phase high-performance liquid chromatography (RP-HPLC), the predominant technique in drug analysis, relies heavily on organic solvents such as acetonitrile, which is known for its chromatographic efficiency, but also for its toxicity and flammability. To address these concerns, it is essential to minimize the use of toxic organic solvents. The aim of this study is to explore greener RP-HPLC modifications and evaluate their applicability in the pharmaceutical industry. Methods were developed for the separation of dronedarone hydrochloride and its degradation products based on experimental design, including micellar liquid chromatography (MLC), β-cyclodextrin (CD) modified RP-HPLC and ultra-high performance liquid chromatography (UHPLC). The eco-friendliness of these methods was assessed using the analytical eco-scale score, green analytical procedure index (GAPI) and analytical greenness (AGREE). AGREE appears to be the most suitable, as it revealed the greatest differences between the compared methods, as well as insights into critical aspects of the methods. UHPLC and β-CD modified RP-HPLC have been shown to be superior to MLC, and both methods can be a good choice, depending on whether the ease of implementation or energy efficiency is considered to be a more important criterion.